The Role of Wideband Tympanometry in the Diagnosis of Meniere's Disease - Meng, Xiangming; Zhu, Kangxu; Yue, Jing; Han, Chengzhou (Frontiers in Neurology, 2022)
Meniere's disease (MD) is a clinical syndrome characterized by spontaneous recurrent vertigo, usually accompanied by hearing loss, tinnitus, and aural fullness. The cause of MD remains unclear and is generally considered to be associated with endolymphatic hydrops. Studies showed that patients with MD could have eustachian tube dysfunction (ETD). ETD can disrupt the pressure balance between the middle and inner ear and impair the inner ear's function. In recent years, several studies have attempted to identify MD by using wideband tympanometry (WBT). However, there are limited studies in this area. There is no consensus on how to use WBT to diagnose Meniere’s disease. Therefore, we endeavored to conduct a narrative review in this aspect based on the latest research findings. Reduction in resonance frequency and absorbance are characteristic of MD and can identify Meniere's disease. The use of an increase in the integrated area of absorbance as an indicator for identifying MD is controversial. WBT seems to be ineffective as a diagnostic tool during the acute episodes of Meniere's disease. Patients with MD may benefit from WBT. WBT has excellent potential for future use in Meniere's disease. However, further large sample sizes, multicenter studies are needed.